Una lengua trabada (o los encajes del oficio) Nota sobre un libro de poemas de Carmen Berenguer. - ARQUEROS, GONZALO (Nomadías)
The article talks about the poetry book "Mama Marx" by Carmen Berenguer. It highlights that the book uses images, sounds, and accumulated words in the language, exploring the body as inscription and mediation. It is mentioned that Berenguer's writing is situated on the boundary between language and the body. Additionally, the book is described as a collection of stamps or stamps, and reference is made to the relationship between nature and merchandise. The inclusion of footnotes at the end of the book that reference Carlos Marx, Sigmund Freud, and Friedrich Nietzsche is also mentioned.